Primary Commodities : Market Developments and Outlook. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1986)
This paper provides an analysis of recent developments relating to the major nonfuel primary commodities (hereafter referred to as commodities) entering international trade. The unit value of manufactured exports in dollar terms also increased every year from 1972 to 1980; the rate of increase was 1 2 percent per annum. The persistent upward trend in dollar prices of commodities that characterized much of the 1970s ended in 1980. In addition to the movements in exchange rates outlined above, which determine the differences in price movements when measured in different currencies, the factors shown in various studies to have the greatest impact on current commodity prices are the rates of world inflation, the level of economic activity in the major markets for primary commodities, and the supply of the commodities concerned. Econometric studies have shown a positive relationship between commodity prices and inflation. In one study, changes in domestic wholesale prices of the industrial countries were found to have a significantly positive relationship to commodity prices with an elasticity of about one.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet